PENGGUNAAN MEDIA KARTU PERAN UNTUK MENINGKATKAN MINAT BELAJAR IPAS DI KELAS IV SD INPRES 6/80 KAWERANG KABUPATEN BONE - Sitti Jauhar; Rosmalah; Ailinyuliani (MACCA : Science-Edu Journal, 2026)
This study is a classroom action research study aimed at increasing interest in learning Natural and Social Sciences (IPAS) in fourth-grade elementary school students through the use of role cards. The study was conducted in two cycles, each consisting of four stages: planning, implementation, observation, and reflection. The subjects were 23 fourth-grade students. Data collection techniques included observations of teacher and student activities during the learning process and a questionnaire on learning interest in IPAS to measure the effectiveness of the intervention. The results showed an increase in student learning interest from cycle I to cycle II. In cycle I, 9 students (39.13%) achieved the learning interest success indicator, while 14 students (60.87%) did not achieve the success indicator. After improving learning in Cycle II by optimizing the use of role cards, all 21 students (91,3%) successfully achieved the learning interest indicator. Furthermore, teacher and student activity also improved, as evidenced by the increase in the percentage of learning implementation from "adequate" in the initial meeting to "good" in the subsequent meeting. Based on the problem formulation, data analysis, and discussion, it can be concluded that the use of role cards can increase interest in learning science in fourth-grade students. Role cards help create an active, enjoyable, and participatory learning environment, encouraging students to be more involved in the learning process. Therefore, role cards are recommended as an alternative learning medium for science in elementary schools to increase student interest. Keywords : Role Cards ; Learning Interest ; Science